1992
DOI: 10.1055/s-2007-1010551
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness and Limitations of Laparoscopy in the Diagnosis of Tuberculous Peritonitis

Abstract: The value of laparoscopy in the diagnosis of tuberculous peritonitis was determined in 32 patients diagnosed histologically as having the condition. In 27 (85%) patients the diagnosis was obtained by laparoscopy combined with peritoneal biopsy. In five patients in whom laparoscopy was unsuccessful, the diagnosis was established by laparotomy. The visually established diagnosis was unreliable and needed histological confirmation. In the ascitic form of tuberculous peritonitis laparoscopy was a safe method which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 0 publications
0
21
1
1
Order By: Relevance
“…Five of the patients with adhesions (6%) were converted to laparotomy in our series and 16% of patients were converted to laparotomy due to adhesions in the series by Mimica et al 69 The most tuberculosis positive histology specimens are intra / retro peritoneal mass (82%), tubercles (80%) and lymph nodes (77%). There was no positive histology at all for tuberculosis in appendix or gall bladder specimens.…”
Section: Endoscopymentioning
confidence: 48%
See 3 more Smart Citations
“…Five of the patients with adhesions (6%) were converted to laparotomy in our series and 16% of patients were converted to laparotomy due to adhesions in the series by Mimica et al 69 The most tuberculosis positive histology specimens are intra / retro peritoneal mass (82%), tubercles (80%) and lymph nodes (77%). There was no positive histology at all for tuberculosis in appendix or gall bladder specimens.…”
Section: Endoscopymentioning
confidence: 48%
“…The conversion rate is acceptable in our patients due to the nature of the disease. Mimica et al 69 reported 16%…”
Section: Perioperative Complications/ Deathsmentioning
confidence: 99%
See 2 more Smart Citations
“…Laparoscopies have been hailed as being particularly useful for obtaining quality samples for microbiological analysis. However, laparoscopic investigation of tuberculous peritonitis has failed in 1% to 16% of cases, [29,36,37] and is not without risk. The major complication is intestinal perforation, [38,39] which was originally thought to be more common in the fibro-adhesive form.…”
Section: Discussionmentioning
confidence: 99%